Rol del trabajador social en la garantía de derechos laborales del trabajador en la compañía minera Tocadulomo S.A. - Huanca Huanca, Rody Germanio (My University, 2020)
By virtue of the fact that Social Work is immersed in the workplace, through this essay it is intended to investigate based on the documentary on the role of the Social Worker in guaranteeing the worker's labor rights, the proposed objective is to analyze the role of the Social worker and its impact on the guarantee of the worker's labor rights in the mining company Tocadulomo S.A. For the development of the degree test, the methodology used was based on bibliographic research validated by the scientific community, with a qualitative approach and based on a humanist intervention model, with its own Social Work guidelines that enhance the research, likewise, in the compilation of information from texts and scientific articles on the role of the Social Worker and in the Constitution of the Republic of Ecuador, the Labor Code that corresponds to the rights of workers in labor matters. The result of the research is that the role of the Social Worker varies according to the intervention, it is possible to mention the most applied as they are; promoter, mediator, planner, manager among others, likewise their intervention is essential in the guarantee of workers' rights, allowing to enforce and access all labor rights articulated in established laws, achieving a harmonious, prosperous, sustainable and labor welfare.
En virtud que el Trabajo Social está inmerso en el ámbito laboral, mediante este ensayo se pretende indagar en base a lo documental sobre el rol del Trabajador Social en la garantía de los derechos laborales del trabajador, el objetivo planteado es analizar el rol del trabajador Social y su incidencia en la garantía de los derechos laborales del trabajador en la compañía minera Tocadulomo S.A. Para el desarrollo del ensayo de titulación la metodología utilizada se basó en la investigación bibliográfica validadas por la comunidad científica, con un enfoque cualitativo y basado en un modelo de intervención humanista, con lineamientos propios de Trabajo Social que le dan un realce a la investigación, así mismo, en la recopilación de información de textos y artículos científicas sobre el rol del Trabajador Social y en la Constitución de la Republica del Ecuador, Código de Trabajo que corresponde a derechos de los trabajadores en materia laboral. El resultado de la investigación es que el rol del Trabajador Social varía de acuerdo a la intervención, se puede mencionar los más aplicados como son; promotor, mediador, planificador, gestor entre otros, así mismo su intervención es esencial en la garantía de derechos de los trabajadores, permitiendo hacer cumplir y acceder a todos los derechos laborales articulados en leyes establecidas, logrando un ambiente armonioso, prospero, sostenible y de bienestar laboral.
Keywords: LEY; TRABAJO SOCIAL; DERECHO; LABORAL